When the light finds us: from a life sentence to a life transformed - Henderson, Judy (Worthy, 2025)
When the Light Finds Us tells the powerful true story of Judy Henderson, a wrongfully convicted mother sentenced to life in prison. Despite decades of injustice, violence, and separation from her children, Henderson held onto hope, advocated for incarcerated women, and ultimately won clemency and a full pardon after nearly 35 years. Her journey is a testament to resilience, justice, and a mother’s unwavering love